Potency of the common: intercultural perspectives about community and individuality - Melville, Gert; Ruta, Carlos Rafael (Challenges of life, 2016)
The central question of the book is as follows: To what extent does the community present a challenge in the life of the individual? Well-known international Philosophers, historians, anthropologists, political scientists, theologians and sociologists attempted to find explications by intercultural comparison.
Gesehen am 11.04.2017
Keywords: Konferenzschrift -- 10.11.2015-13.11.2015 -- Buenos Aires; Ethnische Gruppe; Südamerika; Kulturelle Identität; Gemeinschaft; Individualität